Computational analysis on micro-shunt of minimally invasive glaucoma-surgery (MIGS) in severe glaucoma - Khairulfuaad, Riyadhthusollehan (2021)
Incurable blindness, known as glaucoma, is one of the leading eye diseases ever recorded worldwide. Novel treatment of micro-device implanted in the eye to drained the undesired amount of aqueous humour (AH) has been introduced. MinimallyInvasive Glaucoma-Surgery (MIGS) is a device for controlling the disease. Thus, this study was conducted to evaluate the MIGS micro shunt device’s performances based on the range of intraocular pressure, IOP produced. Four (4) different MIGS devices, namely Cypass, Ex-Press, InnFocus, and Xen Gel micro shunts, were compared according to clinical reports and research article. Computational fluid dynamics (CFD) analysis on the AH hydrodynamics considering glaucomatous condition was done on all four MIGS models. A commercially available CFD ANSYS Fluent version 19.2 was employed for simulation work; the velocity vector analysis and pressure distribution were discussed. An experiment on the fabricated one-part novel simplified laboratory-scale prototype-model was conducted to validate the CFD simulation results. 3D printer technology (Wang et al., 2019) and casting process (Darlis et al., 2017) were used in model fabrication. Water-glycerine solution as the working fluid used in experiment (Darlis et al., 2017). The experimental model produces no leaking problem. In a simulation study, the AH flow behaviour inside the human eye anterior chamber (AC) with the MIGS devices model was discussed. Among those four (4) MIGS) models, InnFocus model, produced an ideal IOP level for glaucoma treatment (1882.2970 Pa to 2658.6641 Pa) and the lowest possibility to cause Pigmentation Dispersion Syndrome (PDS) through wall shear stress (WSS) analysis (maximum WSS of 0.00066 Pa). It also creates medium flow behaviour without any fluctuation and high velocity as compared to the other. The simulation study also shows that the Ex-Press model produces the highest velocity fluctuation and irregularity in its flow behaviour. It also creates the highest level of WSS up to 5.2 Pa on the posterior iris. This finding helps to minimize the percentage of visual impairment caused by glaucoma surgical procedure in Malaysian glaucoma patients and contribute to a global eye health action plan 2020-2025 by World Health Organization (WHO).